The embarrassment of riches: ‘Head’ words in the Indo-European family - Gąsiorowski, Piotr (Yearbook of the Poznan Linguistic Meeting, 2017)
The notion of HEAD is reflected in the basic lexicon of all known languages; the identification of the head as a distinct and vitally important body part, labelled with a simplex word, seems to be a cross-cultural universal. Thanks to their high frequency of use and their “basic concept” status, words meaning ‘head’ tend to be diachronically stable and therefore important for comparative reconstruction. Their expected retention rate – as estimated on the basis of data from several uncontroversial language families – is on a par with words meaning ‘heart’ or ‘foot’. On the other hand, culture-specific factors may lead to the proliferation of secondary meanings, the rise of stylistically marked near-synonyms, and consequently to locally accelerated lexical evolution. This seems to have happened repeatedly in the Indo-European family, in which not only the oldest reconstructible ‘head’ word, *ḱreh₂- but also secondary, branch-specific terms have often been subject to lexical replacement. This unusual variability of words for head in Indo-European contrasts with the remarkable conservatism of words for several other body-part concepts, such as eye, ear, tooth and heart. In this paper, we shall attempt to identify recurrent patterns of semantic change in the emergence of new synonyms and the polysemic development of inherited ‘head’ words. Insights derived from recent studies of “embodiment” will be used to explain the observed tendencies.